Citric Acid Production by Saccharomycopsis Lipolytica Using Batch Culture: Study on Oxygen Requirement - Osman, Rosmawati (1994)
A citric acid producing yeast strain Saccharomycopsis lipolytic 5054 formerly known as Candida lipolytica was used throughout the study. The strain was obtained from Thailand Institute of Scientific and Technological Research (TISTR). A preliminary study on the development for the optimization of the fermentation process was conducted. The experiments included the effect of medium contents such as CaC03 and initial glucose concentrations, inoculum size, agitation rates, KLa (volumetric oxygen transfer coefficient) and dissolved oxygen concentrations. From the preliminary experiments, Medium I (l0% glucose, 0.1% yeast extract, 0.1% MgS04.7H20, 0.2% NH4CI, 0.1% KH2PO, 1% CaC03, pH 6.6) was selected as the fermentation medium throughout the study. The optimum growth temperature and inoculum size was 30°C and 10%, respectively. 1% CaC03 (w/v) was selected as the optimum concentration. The highest KLa obtained was 29.6 hour-I at the agitation rate of 700 rpm using the Rushton turbine impeller. This impeller speed was employed during the studies on optimum dissolved oxygen concentration, where the highest citric acid production obtained was 11.6 giL during fermentation at 50% (20 mg/L) dissolved oxygen concentration. The optimum fermentation period was 50 hours where the exponential phase ended and the stationary phase started.